RELATION BETWEEN LATENT SPECIFIC MOTOR ABILITIES AND SITUATION MOTOR SKILLS WITH VOLLEYBALL PLAYERS AGED FROM 16 TO 17 - Rabit Veseli; Arianit Morina; Musa Selimi; Nazim Myrta; Afrim Selimi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The game of volleyball with its dynamic character is present in the world of the sport with permanent development and growing popularity and fans. Volleyball is part of a pollystructural complex sports activities. It is performed on a ground of a relatively small size (18 x 9 meters) and is a kind of game that requires of players a high level of advanced motoric abilities (speed, strength, endurance, a fast rate of visual reaction, explosivity), as well as specific motoric skills (precision etc.). Scientific conclusion as well as the growing number of conducted researches in the very game, have a real contribution to its modern development and level of popularity. Situation-motoric skills make a significant dimension in the structure of volleyball game. The subject of the research is specific-motoric abilities and situation-motoric skills of 52 volleyball players aged from 16 to 17. The basic goal of the research is to establish the effect of specific-motoric abilities on situation-motoric skills of volleyball players in latent space. In order to assess the specific-motoric abilities 9 tests are used, and to assess the situation-motoric skills 3 precision tests are used. The results obtained from the 12 applied tests are worked out through the basic statistic parameters. Through component factor analysis 3 latent specific-motoric dimensions are isolated as well as one situation-motoric dimension. By regressive analysis there is established a low but statistically significant relation between the criterion and predictor latent dimensions. That confirms the dependence and relation between the specific-motoric abilities and situation-motoric skills. Researches in the fi eld of similar questions have been conducted by the following authors: Jurko et al., 2013 and Nešić, et al., 2011.